Towards an assessment for organizational participatory research health partnerships: A systematic mixed studies review with framework synthesis. (April 2019) - Hamzeh, J.; Pluye, P.; Bush, P.L.; Ruchon, C.; Vedel, I.; Hudon, C.
Highlights: A new model frames the evaluation of researcher- health organization partnerships. The new model includes three axes, Trust, Collective Learning and Sustainability. Each axis has four to five specific dimensions each. A pool of 95 items is presented that operationalizes the new model. Abstract: Within the health sciences, organizational participatory research (OPR) is defined as a blend of research and action, in which academic researchers partner with health organization members. OPR is based on a sound partnership between all stakeholders to improve organizational practices. However, little research on the evaluation of OPR health partnership exists. This systematic mixed studies review sought to produce a new theoretical model that structures the evaluation of the OPR processes and related outcomes of OPR health partnerships. Six bibliographic databases were searched together with grey literature sources for OPR health partnership evaluation questionnaires. Six questionnaires were included, from which a pool of 95 OPR health partnership evaluation items were derived. The included questionnaires were appraised for the quality of their origin, development and measurement properties. A framework synthesis was performed using an existing OPR framework by organizing questionnaire items in a matrix using a hybrid thematic analysis. This led to our proposed Organizational Participatory Research Evaluation Model (OPREM) that includes three axes, Trust, Collective Learning and Sustainability (with specific dimensions) and 95 items. This model provides information to help stakeholders comprehensively structure the evaluation of their partnerships and subsequent improvement; thus, potentially helping to improve health organization practices.